Srikandi Minang yang Memberikan Inspirasi dalam Dunia Pendidikan Sepanjang Masa - Popi Andriani; Salmi Wati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The role of women in education has faced various challenges in the past due to traditional and cultural limitations that hampered their access to education. This research explores the contributions of Rahmah El-Yunusiyah and Rohana Kuddus, two Minangkabau women figures who were pioneers of women's education in Indonesia. Rahmah El-Yunusiyah founded Diniyyah Putri in 1923, creating an education system that focused on forming women with an Islamic spirit and empowerment in society. Rohana Kuddus, through the Amai Setia Craft School which she founded in 1911, fights for women's empowerment through skills and entrepreneurship-based education. This research uses a literature study approach to examine the dynamics of the thinking of these two figures in encouraging women's education, which is an important basis for gender equality in the field of education. The research results show that the education they initiated not only improves women's living standards, but also has a significant influence on social transformation, both at the local and international levels.